استخدام مدخل التعليم البنائي لترقية مهارة الكتابة العربية - Walfajri Walfajri (Institut Agama Islam Negeri (IAIN) Metro, 2017)
The Arabic writing skill is one of the important Arabic language skill and it is a main goal of the Arabic learning as foreign language. However, it does not get a main concern in Arabic teaching as foreign language. Beside, the students’ Arabic writing skill is still in low level. This research aims to increase students’ Arabic writing skill through the constructive teaching approach and to describe the effective teaching method of Arabic writing skill as foreign language. This research used the classroom action research method conducted in two cycles. Each cycle consists of four steps they are: 1)planning, 2) action, 3) observation, and 4) reflection. The data of research consist of teaching and learning process of Arabic writing skill in classroom and students’ Arabic compositions. The research participants are a lecture and 30 students of Arabic writing skill. The results of research showed that the Arabic writing skill teaching through the constructive approach consists of three phases they are: 1) pre writing phase, 2) writing phase, and 3) post writing phase. The results also showed that the constructive teaching approach is effective to increase students’ Arabic writing skill.